x-2=39

Simple and best practice solution for x-2=39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-2=39 equation:


Simplifying
x + -2 = 39

Reorder the terms:
-2 + x = 39

Solving
-2 + x = 39

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + x = 39 + 2

Combine like terms: -2 + 2 = 0
0 + x = 39 + 2
x = 39 + 2

Combine like terms: 39 + 2 = 41
x = 41

Simplifying
x = 41

See similar equations:

| 3x+22=10-34 | | 3(3x+2)=x+7 | | 2x+24=4x+10 | | 48446+-7685x= | | x^4+6x^3-8x-48=0 | | 4x^3+3x-2=0 | | -14764+5543x= | | w=-14764+5543x | | w=51x-900x+6392x-14764 | | m=54x+1864x-9603x+48446 | | (s^3)-(3s^2)-s+6=0 | | 2-(x-1)=3-2X | | y-19y+77= | | (4n-n-3)-(-3n-n-2)= | | x+3x-9x-27= | | -1=a+b+c | | -16t+16t+32= | | -5-4x=3x-7 | | 65x^2+24x-432=0 | | 65x^2=24x-432 | | -2+8x=10+3x | | 6-2x=-9-7x | | -3x+7=7x-3 | | 2-3u=-13 | | 3t-2=5+4t | | 8x-3=4x+5 | | HalfK=16 | | 1.5x-0.5=0 | | x+3=0whatisy | | 6x+3(x-2)=39 | | 9x^7-27x^4+45x^6= | | (3x-18)(-x+8)=0 |

Equations solver categories